One-pot fluorescent labeling protocol for complex hydroxylated bioactive natural products - Haldar, Saikat; Kumar, Santosh; Kolet, Swati P.; Patil, Harshal S.; Kumar, Dhiraj; Kundu, Gopal C.; Thulasiram, Hirekodathakallu V. (Journal of Organic Chemistry, 2013)
Tagging of small bioactive molecules with a fluorophore is a highly sensitive method to trace their cellular activities through real-time visual information. Here we disclose a 7-nitrobenzo-2-oxa-1,3-diazole (NBD)-based, high-yielding, one-pot labeling protocol for hydroxylated molecules using Yamaguchi coupling as the key reaction. This methodology was successfully applied on several sensitive and complex hydroxylated bioactive compounds including 7-deacetylazadiradione, simvastatin, camptothecin, andrographolide, cinchonine, beta-dihydroartemisinin, and azadirachtin A. Further, utility of this protocol was illustrated on the cytotoxic activity of azadiradione derivatives against several cancer cell lines through cell imaging of two qualified fluorescent probes.

Overexpression of squalene synthase in withania somnifera leads to enhanced withanolide biosynthesis - Patel, Neha; Patel, Parth; Kendurkar, Shuchishweta V.; Thulasiram, Hirekodathakallu V.; Khan, Bashir Mohammad (Plant Cell Tissue and Organ Culture, 2015)
Genetic engineering of secondary metabolic pathways is an emerging area of research for production and improvement of natural products in plant biotechnology. Here, we describe a systematic approach to manipulate a key regulatory step of isoprenoid biosynthetic pathway in Withania somnifera to study its effect on withanolide production. We generated T-0 W. somnifera plants overexpressing squalene synthase (WsSQS) by Agrobacterium tumefaciens mediated transformation, which were analyzed by Gus biochemical assay and PCR of hygromycin phosphotransferase (hptII) and WsSQS. qRT-PCR analyses of various transformed tissues indicated 2-5 fold increase in WsSQS transcripts in both T-0 and T-1 generations. The tissue specific protein expression studies revealed 2-3 fold increase in WsSQS, which was further confirmed by enzyme activity. These observations were corroborated with the 1.5-2 fold increase in total withanolide content of the transformed tissues. However, in leaf tissue, the levels of Withaferin A and Withanolide A increased significantly up to 4-4.5 fold. These findings demonstrate genetic engineering of isoprenoid pathway in W. somnifera resulting in enhanced production of withanolides, and also provide insights into such metabolic pathways for their manipulation to improve the pharmacological content of different medicinally important plants.
Keywords: Agrobacterium tumefaciens; Solanaceae; Squalene synthase; Withania somnifera; Withanolides

Oral feeding with polyunsaturated fatty acids fosters hematopoiesis and thrombopoiesis in healthy and bone marrow-transplanted mice - Limbkar, Kedar; Dhenge, Ankita; Jadhav, Dipesh D.; Thulasiram, Hirekodathakallu V.; Kale, Vaijayanti; Limaye, Lalita (Journal of Nutritional Biochemistry, 2017)
Hematopoietic stem cells play the vital role of maintaining appropriate levels of cells in blood. Therefore, regulation of their fate is essential for their effective therapeutic use. Here we report the role of polyunsaturated fatty acids (PUFAs) in regulating hematopoiesis which has not been explored well so far. Mice were fed daily for 10 days with n-6/n-3 PUFAs, viz. linoleic acid (LA), arachidonic acid (AA), alpha-linolenic acid and docosahexanoic acid (DHA) in four separate test groups with phosphate-buffered saline fed mice as control set. The bone marrow cells of PUFA-fed mice showed a significantly higher hematopoiesis as assessed using side population, Lin-Sca-1(+)ckit+, colony-forming unit (CFU), long-term culture, CFU-spleen assay and engraftment potential as compared to the control set. Thrombopoiesis was also stimulated in PUFA-fed mice. A combination of DHA and AA was found to be more effective than when either was fed individually. Higher incorporation of PUFAs as well as products of their metabolism was observed in the bone marrow cells of PUFA-fed mice. A stimulation of the Wnt, CXCR4 and Notch1 pathways was observed in PUFA-fed mice. The clinical relevance of this study was evident when bone marrow-transplanted recipient mice, which were fed with PUFAs, showed higher engraftment of donor cells, suggesting that the bone marrow microenvironment may also be stimulated by feeding with PUFAs. These data indicate that oral administration of PUFAs in mice stimulates hematopoiesis and thrombopoiesis and could serve as a valuable supplemental therapy in situations of hematopoietic failure. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Bone Marrow Transplantation (Bmt); Cord Blood; Down-regulation; Ex-vivo Expansion; Hematopoiesis; Hematopoietic Stem Cells (Hscs); Lipid rafts; Myocardial-infarction; Polyunsaturated Fatty Acids; Progenitor Cells; Prostaglandin-e2; Self-renewal; Spleen Colonies; Stem-cell Proliferation; Thrombopoiesis